Degenerated fibroid: a diagnostic dilemma - Gaur, Nayanika; Jha, Manish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Leiomyoma is one of the most commonly encountered benign gynaecological neoplasms. With a wide range of symptoms, sometimes even asymptomatic, these tumors are easy to diagnose and treat, unless there are degenerative changes, which makes them difficult to diagnose and differentiating them from other serious conditions including malignancy, thereby, complicating their management also. Here, the case present to you a case of 48-year-old women with symptoms and clinical examination suggesting fibroid uterus but imaging studies inconclusive to differentiate fibroid uterus with ovarian malignancy, thus, creating a diagnostic dilemma. Ultimately, patient underwent exploratory laparotomy, keeping possibility of ovarian malignancy. Histopathological examination of the specimen of total abdominal hysterectomy with bilateral salpingo-oopherectomy concluded extensive cystic degeneration of leiomyoma and no evidence of malignancy.